Reaktualisasi Karakter Peserta Didik melalui Pendidikan Islam - Didik Supriyanto; Arif Efendi (MODELING: Jurnal Program Studi PGMI, 2021)
This article discusses the role of Islamic religious education in character building of students in schools. PAI is one of the main pillars of character education. Character education will develop well if it starts from the deep-rooted religious spirit of children, so the school's PAI teaching materials are one of the supporting characters of character education. Through PAI studies, students learn aqidah as the foundation of their religion, teach the Quran and Hadith as a guide for their lives, teach Fiqh as a legal sign in worship, teach Islamic history as a living example, and teach ethics as a human guide. good or bad behavior. Bad. Therefore, the main goal of PAI learning is the personality development of the students, which is reflected in their behavior and mentality in everyday life. One of the successes of PAI learning in schools depends on the application of appropriate learning methods.